Social Psychology and Investigations of History - Mulevičius, Leonas (Problemos, 1970)
The paper presents a historiographical review of the works of historians, psychologists, and philosophers on the named subject. The author develops the idea of social psychology being a multilateral phenomenon in history. The investigator should take into account social-individual and group-psychology of actual event partakers – representatives of different social groups and classes as well as social psychology of event contemporaries and non-contemporaries, who had assessed the events before him. Examples of how underestimation of this can lead to distortion or modernization of reality are given. Social psychology assists in deeper analysis of not only political life, class struggle and culture but economic life as well. Reference is made to sources to be addressed in the investigation of social psychology in the past.